PERSEPSI KONSUMEN TERHADAP MEREK FASHION MUSLIMAH DI INDONESIA - Andi Ika Fahrika; Murtiadi Awaluddin; Amiruddin K (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2023)
Muslimah clothing is defined as clothing or clothing that conforms to Islamic law, that is, clothing that is not tight (shapes the curves of the body), and the person wearing the clothing is a Muslim woman who follows her religious teachings in accordance with Islamic dress code. Currently, the Indonesian industrial sector is paying attention to the Muslimah fashion community. A Muslimah consumer will also provide an assessment or provide the largest contribution to consumer perceptions of a particular product brand. Considering that the brand in question is a good brand and is the only company's most valuable asset and has a certain impact for every consumer who has an impact on the general public will experience a positive feeling related to certain products and businesses. The aim of this study is to explain how consumers perceive Muslimah fashion brands and also how Indonesian consumers view Muslimah entrepreneurs. This type of research is qualitative research using library research methods. The data used in this study are primary and secondary. While the data analysis technique used in this study is content analysis. The results of this study indicate that the brand is an extrinsic stimulus that influences consumer perceptions of a particular item.Â